The Symbolic Meaning of Ulul Albab in the Qur’an: A Semiotic Study by Roland Barthes: Makna Simbolik Ulul Albab dalam Al-Qur’an: Kajian Semiotika Roland Barthes - Pendi Nurul Azmi; Muliadi Muliadi (Senarai: Journal of Islamic Heritage and Civilization, 2025)
This study aims to analyze the meaning of the term Ulul Albab in the Qur'an using Roland Barthes’ semiotic approach. The concept of Ulul Albab frequently appears in various verses to refer to a group of people endowed with profound intellectual and spiritual depth. According to Barthes’ theory, every sign possesses two levels of meaning: denotative (literal meaning) and connotative (symbolic/cultural meaning). Through this framework, the study explores the lexical meaning of Ulul Albab and maps the symbolic meanings embedded within it in the context of Islamic culture, ethics, and spirituality. The findings indicate that Ulul Albab refers not only to rational intelligence but also carries deep symbolism of transcendental awareness. This research is expected to contribute to the interdisciplinary approach in Qur’anic exegesis, particularly in the study of meaning and the philosophy of signs.